Applied business research: an empirical study on customer satisfaction at the Royal Malaysia Customs department Ipoh / Salehhudin Abd Rahman, Muhamad Fauzi Abdul Karim and Muhammad Jafari Abdul Hamid - Abd Rahman, Salehhudin; Abdul Karim, Muhamad Fauzi; Abdul Hamid, Muhammad Jafari (2007)
The research literature on customer satisfaction appears to be endless and is growing in popularity throughout the years. Despite the growing number of models available for measuring customer satisfaction, SERVQUAL appears to be the starting point towards further research. This study hopes to add further contribution towards understanding and measuring customer satisfaction in the quest for service improvements. Although the major focus of most studies on customer satisfaction were aimed towards improving services provided by the private sector, it is undeniably important too that customer satisfaction towards public sector bodies would be translated into an efficient and an effective delivery system as envisaged by the government of the day in order to serve the rakyat better- particularly in today's age of globalization. The purpose of this study is to evaluate the services quality of the Royal Malaysia Customs Department at its Ipoh office from the clients' viewpoints and to gauge the level of customer satisfaction. In addition, it intends to focus on the dissatisfied customers; to seek customer perception on the overall image the Royal Malaysia Customs Perak; and to recommend measures that can be taken towards improving customer satisfaction and hence turnaround the image of Royal Malaysia Customs Perak. The study was conducted on 360 clients of the Department from various entities that were directly or indirectly related on matters relating to the legal provisions administered by the Royal Malaysia Customs Department.